Leaning Against the Wind : Fiscal Policy in Latin America and the Caribbean in a Historical Perspective - Vegh, Carlos; Lederman, Daniel; Bennett, Federico R. (World Bank, Washington, DC, 2017)
This report by the Office of the Chief Economist for Latin America and the Caribbean (LAC) of the World Bank studies the region’s fiscal policies. After reviewing LAC’s growth performance, Chapter 1 provides an accounting of its financing needs during the 21st Century to understand how such a diverse region ended up with fiscal deficits across the board in 2016. Chapter 2 goes back to the 1960s and assesses the cyclical properties of fiscal policies. LAC, like most developing countries and in contrast with most developed economies, exhibited procyclical fiscal policies. Good news arrived in the 2000s: one in three economies became countercyclical, which helped improve credit ratings. Yet fiscal policy is complicated by our inability to know if current economic conditions are temporary or permanent. The report argues for a prudent stance that would err on the side of saving too much during upswings and perhaps borrowing too little during downturns.